A Grave from Nezabylice, Chomutov District. On the Phenomenon of Inhumation in Stage B1 of the Early Roman Period in Bohemia - Půlpánová-Reszczyńska, Agnieszka; Kuljavceva Hlavová, Jana; Ondráčková, Lenka; Černochová, Radka; Křivánek, Roman; Radoň, Miroslav; Půlpán, Marek (Analecta Archaeologica Ressoviensia, 2023)
The article describes the discovery of a skeletal grave in 2015 in Nezabylice (NW Bohemia, Chomutov district) at a cremation burial ground, which was dated to stage B1 of the early Roman period according to characteristic metal objects. Today, only four dozen similarly dated skeletal graves are registered in Bohemia, which, together with the early date of acquisition, makes them one of the rarest and most difficult to recognize archaeological monuments in this area. In the given situation, every recently researched skeleton grave from the early Roman period brings a wealth of new and important information about this distinctive phenomenon of burial rite among the Elbe-Germanic tribes.